(untitled) (Revista Linhas, 2026)
This text combines theoretical reflection and empirical research on curriculum in cyberculture, and the challenges posed to teachers. This work addresses the curriculum in cyberculture based on the mobility of online research and teaching, with app-learning practices. The authors understand the process of teaching and researching based on the sharing of knowledge through the mediation of digital interfaces, conceived as devices for the emergence of curricula in cyberculture, a scenario that was consolidated with mobile technologies. In this sense, they seek to understand teachers’ thoughts on the use of mobile technologies, bringing data from a study carried out in six European countries. When revealing that teachers have an important responsibility as agents of school transformation, the text concludes with a discussion on the competencies of these professionals, grounded in an informed reflection based on the exploration and experimentation of the pedagogical potential that digital technologies can offer in curricular practices.